Istikhdam Teknolojiā li at-Ta'līm 'an Bu'd fī Qism Ta'līm al-Lughaħ al-'Arabiyaħ bi Jāmi'aħ ar-Rāyaħ li al-Banāt: استخدام تكنولوجيا للتعليم عن بعد في قسم تعليم اللغة العربية بجامعة الراية للبنات - Jannah, Nidaul; Harvina H, Lola; Qurani, Ainun Suci; Jannah, Yeni Prihatin Miftahul; Hilmi, Danial (PT. Student Rihlah Indonesia, 2024)
Technology at this time has penetrated all areas of human life, especially the field of education. The purpose of this study is to describe the technology used in distance education in STIBA Ar Raayah Sukabumi Arabic Language Education Study Program for Women. This research uses a qualitative approach and a case study approach, and data collection through questionnaires and field observations. The research results obtained are, first: distance education in the STIBA Ar Raayah Arabic Language Education Study Program for Girls uses the Google Meet program and several devices placed in the student's classroom, namely: cameras and microphones; In the female students' classroom: computers, cell phones, screens or televisions, projectors, loudspeakers, and microphones This education requires an international network. The conclusion of this research shows that distance education has weaknesses and problems that must be resolved.